Switching Behaviour in Using Islamic Digital Banks in Indonesia: Push-Pull Mooring Model - Albanna, Hasan; lutpika, Ika (Journal of Finance and Islamic Banking, 2022)
This study aims to analyse the factors influencing customers’ switching behaviour in the use of digital banking from the perspective of the PPM model. A self-administered questionnaire was used to collect the data. PLS-SEM was used to analyse the data. The results showed that alternative attractiveness, response to a service failure, and push factors positively influence switching intention behaviour. Switching cost as a mooring factor positively influences switching intention behaviour. Meanwhile, switching intention influences switching behaviour. However, alternative attractiveness and involuntary switching as pull factors negatively affect switching intention behaviour. Several studies have been conducted on switching intention behaviour in the use of digital banking products and services. However, studies on the switching intention behaviour of Islamic digital bank products and services are scarce. This study contributes to the literature on switching behaviour in the use of Islamic digital banks.